Common issues in diabetes - Abdullah Al-Mahmood, Sinan Mohammed; Ahmad Arifin, Syamsul; Firdaus, Mohd Khairul Zul Hasymi (IIUM Press, International Islamic University Malaysia, 2017)
Diabetes mellitus (DM) is a chronic medical condition that can attack many people regardless age and gender, and which is defined as that condition where there is too much glucose in the bloodstream. DM occurs when body cannot use insulin very well or the pancreas is unable to produce enough insulin to process ingested sugars. This study revealed that the vast majority of patients registered with the outpatient clinic at Hospital Tengku Ampuan Afzan (HTAA) have uncontrolled diabetes; the risk factors for uncontrolled diabetes include being female and over 40 years old, which indicates that this was most prevalent among those with type 2 diabetes. Based on the findings of the current study, the majority of caregivers have a high awareness of diabetic foot care. More than half of the caregivers claim that they have received information about diabetic foot care. In terms of sociodemographic data factors, the study indicated that age, race, religion, education level, and monthly family income are independent variables that are not related to the level of awareness among caregivers about diabetic foot care.This study showed that public in Kuantan, Pahang Darul Makmur, has a low level of knowledge about maggot therapy treatment in diabetic foot ulcers (DFU) healing and that a high number of people thus tend to reject maggot therapy treatment. Based on the outcomes, the majority of DM type 2 respondents were identified as having high self-efficacy beliefs, suggesting they had confidence in caring for their own feet. In terms of actual foot-care behaviours, both in the past week and in general, the majority of respondents displayed good practice. However, there was no significant association shown between foot-care self-efficacy beliefs and actual foot-care behaviour in the past week or in general.Finally, the findings of this study suggest that the prevalence of gestational diabetes mellitus (GDM) at the Maternal and Child Health Clinic Indera Mahkota was higher than in other similar studies. It also demonstrated that higher maternal age, higher body mass index (BMI) and a history of GDM were factors associated with increased risk of developing gestational DM.